ANALISIS YURIDIS KEPASTIAN HUKUM KEPEMILIKAN HAK ATAS TANAH BERDASARKAN BUKTI PUTUSAN LANDRAAD ZAMAN BELANDA DAN SERTIFIKAT HAK MILIK ATAS TANAH (STUDI KASUS PUTUSAN NOMOR : 06/PDT.G/2004/PN.PSP) - AYUNDA SRYKANDY (PREMISE LAW JURNAL, 2016)
Since the Agrarian Law No.5/1960 was issued, all types of dualism in land rights In Indonesia, which was inherited from the Dutch colonialism, have conversed the ownership of land, along with the adat land. According to the verdict of Padangsidimpuan District Court No. 06/Pdt.G/2004/PN.Psp, the plaintif was the heir of the land which was obtained from the Landraad verdict with the land as an adat land. Meanwhile , the plaintiffs complaint was referred to the illegal at by the respondent which was evident in the Court hearing that they had issued the Declaration of Heirs, the Letter of Notifiation of Heir, and controlled the land rights owned by the plaintiff. Later, it had been transferred to another respondent so that it was evident that the transfer caused written judicial evidence, a land rights certificate in the name of the respondent. The judge finally gave a verdict which stated that the respondent was guilty by the legal consideration of written evidence in the Court and the witness testimonies which stated that plaintiff was the person who had the right for the land, while the respondent’s land rights had no legal enforcement and legally null and void. Therefore , it was necessary to study the enforcement of legal certainty in land ownership on the Landraad Verdict and the legality when a person had the evidence of land rights certificate. Keywords : Landraad Verdict, Certificate,Land Rights